Comparison of Membrane Filtration and Replica Plate Technique to Detect Fecal Coliform - Gautam, Bikram; Adhikari, Rameshwar (Medical Journal of Shree Birendra Hospital, 2018)
Introduction: Membrane filtration (MF) is one of the widely used technique on a routine basis. On the other hand, replica plate (RP) technique can be used to transfer existing bacterial colonies in two plates which even allows pinpointing the original colony. The aim of this study is to comparatively detect the cfu/100 mL of fecal coliform using membrane filtration and replica plate techniques. Methods: In the study, a total of 25 bottled water were selected from the local market in Kathmandu valley. The total coliform count was detected using MF, while fecal coliform was detected using both MF and RP technique. Results: It was found that the average cfu/100 mL for total coliform, fecal coliform (MF) and fecal coliform (RP) were 143.38, 49.82 and 51.00 respectively. Pearson correlation coefficient calculated between total coliform and fecal coliform (MF), total coliform and fecal coliform (RP), fecal coliform (MF) and fecal coliform (RP) were found to be 0.695, 0.733 and 0.990 respectively; implying a positive correlation Conclusions: It has been demonstrated that intrinsic and extrinsic factors influence colony forming units. Furthermore, RP is a more sensitive method for screening fecal coliforms although both MF and RP can be efficiently used.